Pemberdayaan Masyarakat Pembudidaya Ikan Nila di Desa Paya Udang Kecamatan Seruway Kabupaten Aceh Tamiang - Sandry Maulijar; Julia Ananda; Naila Fauziah; Septi Masnuria Siregar; Sayed Latiful Ashrori; Zidni Ilman Navia (Jurnal Pengabdian Pada Masyarakat, 2022)
Paya Udang is a village located in Seruway sub-district, Aceh Tamiang district, Aceh Province. Due to the lack of understanding related to community aquaculture management in managing freshwater fish farming in Paya Udang village, it is necessary to conduct aquaculture management training. The purpose of this training activity is to equip the Paya Udang village community in tilapia cultivation activities. This activity was carried out in Paya Udang village, Seruway sub-district, Aceh Tamiang district, involving 6 participants. The method used is a Participatory Rural Appraisal (PRA) and Community development approach. The result of this training activity is an increase in the knowledge of the members of the PEMUDA JAYA cultivation group in the cultivation of freshwater fish, especially tilapia.